L’absolution judiciaire ou la réclamation mensongère - Faribault, Bernard (Assurances)

(untitled) (HEC Montréal, 1986)
In recent years, there have been numerous articles and judgments dealing with article 2474 of the Civil Code with regard to deceitful representations in insurance claims. Some judgments invalidate the deceit-tainted claim completely, others invalidate it in part only while others still are limited to substracting from the claim the object of deceit. Me. Faribault takes a new look at this problem and suggests that a liberal interpretation is unwarranted.